Class, Social Mobility, and Voting: Evidence from Historical Voting Records - Torun Dewan; Christopher Kam; Jaakko Meriläinen; Janne Tukiainen (Aboa Centre for Economics (ACE), 2021)
We explore the connection between social class, social mobility, and voting behavior in nineteenth-century England. To avoid pitfalls associated with survey or aggregate data on voting behavior, we use administrative longitudinal records preceding secret ballot on voters' choices and occupation. These data reveal that the landed gentry, farm workers, non-skilled workers and white-collar workers voted, on average, more for the Conservatives, and petty bourgeoisie and skilled workers for the Liberals. The changes in voting behavior within individuals due to social mobility are immediate and mainly consistent with the same cleavage. Our interpretation is that voting was influenced by economic incentives.
Keywords: D72; N33; N93; 330; Class-based voting; economic voting; social mobility; voting behavior; poll books